When passion is not enough: a study on how a football club can tackle inflation and turnover - the SL Benfica case - Branco, Luís (2022)
The football industry has developed significantly over the past few decades and evolved into something more complicated than merely entertainment or sports. SL Benfica is one of the most successful sports organizations in Portugal and Europe, however the Club is not indifferent to the disruption and trends of the labor market. The goal of this dissertation was to identify approaches that may be used to address the Club's difficulties in a variety of contexts, with an emphasis on the corporate framework and a propensity to highlight best practices in the different business sectors